2022
DOI: 10.21037/atm-22-109
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of serum tumor marker normalization in the perioperative period for patients with advanced gastric cancer

Abstract: Background: Neoadjuvant chemotherapy (NCT) was developed to improve the prognosis of patients with advanced gastric cancer (AGC). Some studies have confirmed the diagnostic and prognostic value of various serum tumor markers in gastric cancer. However, most of these studies were focused on the value of preoperative and postoperative tumor markers in patients undergoing surgery with or without adjuvant therapy, and only a few studies focused on AGC patients undergoing NCT. Methods:We retrospectively analyzed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 12 publications
(10 reference statements)
0
7
0
Order By: Relevance
“…While surgery remains the primary treatment for GC, radical gastrectomy is only suitable for patients diagnosed with early GC. Unfortunately, 50–60% of patients are typically diagnosed in advanced stages, with invasion or metastasis 2 . After radical surgery, patients with locally advanced gastric cancer (LAGC), which refers to the stage between early GC and advanced GC, face high rates of distant metastasis and local recurrence, ranging from 40 to 51% 3 .…”
Section: Introductionmentioning
confidence: 99%
“…While surgery remains the primary treatment for GC, radical gastrectomy is only suitable for patients diagnosed with early GC. Unfortunately, 50–60% of patients are typically diagnosed in advanced stages, with invasion or metastasis 2 . After radical surgery, patients with locally advanced gastric cancer (LAGC), which refers to the stage between early GC and advanced GC, face high rates of distant metastasis and local recurrence, ranging from 40 to 51% 3 .…”
Section: Introductionmentioning
confidence: 99%
“…As an easily accessible clinical examination, CA125 also played a key role in the diagnosis of gastrointestinal malignant tumors [ 18 , 19 ]. Studies have shown that CA125 level was a predictive factor of peritoneal metastases in gastric cancer [ 20 , 21 ] and normalization of CA125 was relevant with better survival [ 22 ]. Thus, we assumed that CA125 level has an impact on the prognosis of GIST patients.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Hu et al . [36]. found that the tumor markers before and after neoadjuvant chemotherapy have a discriminatory ability for patients with GC, and the normalization of tumor markers was associated with better survival.…”
Section: Discussionmentioning
confidence: 99%